2017
DOI: 10.15386/cjmed-701
|View full text |Cite
|
Sign up to set email alerts
|

The Determination Factors of Left-Right Asymmetry Disorders - a Short Review

Abstract: Laterality defects in humans, situs inversus and heterotaxy, are rare disorders, with an incidence of 1:8000 to 1:10 000 in the general population, and a multifactorial etiology. It has been proved that 1.44/10 000 of all cardiac problems are associated with malformations of left-right asymmetry and heterotaxy accounts for 3% of all congenital heart defects. It is considered that defects of situs appear due to genetic and environmental factors. Also, there is evidence that the ciliopathies (defects of structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 111 publications
0
19
0
Order By: Relevance
“…5,6 Cells in the node have a single motile cilium and these cilia generate with a rotational motion a leftward flow of the perinodal fluid that transports morphogenic proteins. 3,4,5,7 This motion would explain the asymmetric transfer of certain genes. The combination of situs abnormalities and primary ciliary dysfunction in human syndromes would strongly support this model.…”
Section: Embriologymentioning
confidence: 98%
See 2 more Smart Citations
“…5,6 Cells in the node have a single motile cilium and these cilia generate with a rotational motion a leftward flow of the perinodal fluid that transports morphogenic proteins. 3,4,5,7 This motion would explain the asymmetric transfer of certain genes. The combination of situs abnormalities and primary ciliary dysfunction in human syndromes would strongly support this model.…”
Section: Embriologymentioning
confidence: 98%
“…5 An alternative theory suggests that increased calcium levels in endodermal cells to the left of the node play an important role in the asymmetric development of organs. 7,8…”
Section: Embriologymentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of laterality disorders has been explored for over two decades, with a consensus that their etiology is multifactorial with genetic and environmental contributions (6,7). The development of laterality disor-…”
Section: Images In Forensic Pathologymentioning
confidence: 99%
“…Congenital heart defects (CHDs) are the most common type of birth defect, affecting close to 1% of live births worldwide 1 . They are thought to be caused by a combination of genetic and environmental factors 2 . However, only a small fraction of CHDs can be attributed to heritable gene mutations and the same CHD mutations can cause a variety of disease phenotypes, suggesting the involvement of modifier genes as well as non-genetic factors 3-5 . In human populations, epidemiology studies showed that occupational or accidental exposure to environmental chemicals such as dioxins can lead to increased congenital defects in newborns and ischemic heart diseases in adults [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%